2015
DOI: 10.1021/acsami.5b00563
|View full text |Cite
|
Sign up to set email alerts
|

New Life for an Old Antibiotic

Abstract: Restoring the antibacterial properties of existing antibiotics is of great concern. Herein, we present, for the first time, the formation and deposition of stable antibiotic nanoparticles (NPs) on graphene oxide (GO) sheets by a facile one-step sonochemical technique. Sonochemically synthesized graphene oxide/tetracycline (GO/TET) composite shows enhanced activity against both sensitive and resistant Staphylococcus aureus (S. aureus). The size and deposition of tetracycline (TET) nanoparticles on GO can be con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 62 publications
0
13
1
1
Order By: Relevance
“…In contrast, Mishra et al. showed that GO alone did not affect bacteria at a concentration ˃1 mg/ml . In our study, the concentration was lower than mentioned concentration.…”
Section: Resultscontrasting
confidence: 93%
See 2 more Smart Citations
“…In contrast, Mishra et al. showed that GO alone did not affect bacteria at a concentration ˃1 mg/ml . In our study, the concentration was lower than mentioned concentration.…”
Section: Resultscontrasting
confidence: 93%
“…Inactivation of PBPs interferes with the cross‐linkage of peptidoglycan chains necessary for bacterial cell wall strength and rigidity. Hence, the bactericidal activity of ampicillin results from the inhibition of cell wall synthesis and is mediated through ampicillin binding to penicillin‐binding proteins (PBPs) …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The nano-sized transformation of another antibiotic TET also improved its bactericidal activity, killing both TET sensitive and resistant bacteria (Shimanovich and Lipovsky 2015). Sonochemically synthesised graphene oxide/TET nanocomposites demonstrated enhanced activity against both sensitive and resistant S. aureus when compared to the same concentration of non-transformed antibiotic (Mishra and Segal 2015). TET loaded in protein microspheres showed high bactericidal effect against E. coli and S. aureus (Avivi and Nitzan 2003).…”
Section: Cationic Antibacterial Polymersmentioning
confidence: 97%
“…There have been many structural alteration studies on antibiotics to struggle against this phenomenon [48]. Because of the potential antibacterial applications of graphene and graphene-based nanocomposites [49], conjugation of existing antibiotics with graphene-based materials is a promising solution to prevent antibacterial resistance [50,51].…”
Section: Microbiological Performance Of Water Purified By Gomentioning
confidence: 99%